PENGEMBANGAN INSTRUMEN PENILAIAN AUTENTIK KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI - Khasanah Khasanah; Mistinurasih Mistinurasih (Akademika : Jurnal Teknologi Pendidikan, 2023)
This study aims to develop an authentic assessment instrument for writing observation report text skills in vocational high schools and produce an authentic assessment instrument for writing observation report text skills that are valid. This research was conducted at a Vocational High School in Bekasi, which has implemented the 2013 curriculum. The techniques used to obtain research materials were observation, interviews, and documentation. This study uses the Research & Development model development from Borg & Gall. The results of this study were 1) implementation of authentic assessment at Bina Insan Kamil Vocational High School using lesson plans and assessment rubrics in the textbook, 2) valid and reliable observation report text writing skill instruments were obtained through expert review, small and large scale trials.